Pengaruh Motivasi dan Kompensasi terhadap Kinerja Karyawan Puskesmas Jambesari - Via Lailatur Rizki (JEBIM Prima, 2023)
This study aims to test and analyze the influence of motivation and compensation on performance of employees at Puskesmas Jambesari. This study uses a quantitative approach that is hypothesisi testing. Methods of data analysis is multiple regressin analysis. The population used was all employess of the Puskesmas Jambesari, and the sampling used census method 51 employees. The results showed that motivation has no significant on employees performance of the Puskesmas Jambesari. Compensation has a significant on employees Puskesmas Jambesari. Motivation and compensation both have a sign has a significant on employees Puskesmas Jambesari.